2013
DOI: 10.1093/jpepsy/jst018
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child Communication and Maternal Depressive Symptoms in Families of Children With Cancer: Integrating Macro and Micro Levels of Analysis

Abstract: Findings suggest concrete targets for improving communication in families after diagnosis or relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
1
23
1
1
Order By: Relevance
“…Second, similar to a previous study, which reported that approximately 45% of the mothers of pediatric cancer patients meet the criteria for clinical depression [14], approximately 51% of the caregivers in our study experienced clinically significant depression during their children's treatment periods. We found that caregivers with depression experienced significantly more distress compared to caregivers without depression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Second, similar to a previous study, which reported that approximately 45% of the mothers of pediatric cancer patients meet the criteria for clinical depression [14], approximately 51% of the caregivers in our study experienced clinically significant depression during their children's treatment periods. We found that caregivers with depression experienced significantly more distress compared to caregivers without depression.…”
Section: Discussionsupporting
confidence: 87%
“…In a study of children in active treatment for brain or bone tumors, 72% of their parents reported depressive symptoms [13]. Additionally, depressed parents tend to be less warm, supportive, and responsive and more hostile towards their child with cancer; in contrast, the absence of depression has been found to predict parents' optimism [14,15]. Depressed parents may be more vulnerable when adjusting to their child's cancer and to various conflicts that might arise.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were grouped into four depressive symptom categories based on their BDI-II score: (1) No to Minimal (0–13), (2) Mild (14–19), (3) Moderate (20–28), and (4) Severe (29–63).This scoring method is recommended by the test authors as a means of minimizing false negatives (Beck). Previous studies in samples with chronic conditions also have used this scoring system (Carney, Ulmer, Edinger, Krystal, & Knauss, 2009; Gannotti, Minter, Chambers, Smith, & Tylkowski, 2011; Rodriguez et al, 2013). “No to Minimal” was used as the reference category.…”
Section: Discussionmentioning
confidence: 99%
“…maintaining the same topic as the child, maternal reflections on children's contributions to the illness-related discussion). 81 Mothers with more symptoms of depression were rated by observers as having a more negative communication style and were less warm, supportive and responsive when interacting with their child. 81…”
Section: Parental Emotional Wellbeingmentioning
confidence: 99%